MONETIZATION STRATEGY FOR MARGINAL GAS PROJECT CASE STUDY OF NORTH KAL PSC PT PERTAMINA HULU ENERGI (PHE) - Wuriastuti Mulyandari, Andini
North Kal is one of exploratory oil and gas fields in Indonesia. The exploration activities to find hydrocarbon accumulation in North Kal block has started since 2004 until some proven resources were found on BDK field on 2013, and followed by discovery of PRG field on 2017. The next challenge for the PSC operator is then to formulate a robust monetization strategy to develop the block, considering the location in captive market area with minimum infrastructure and undeveloped industries. Several development scenarios have been assessed based on techno-economic standpoint to find the most optimum development strategy that gives acceptable return for the contractor. Significant high capital expenditures are required to develop these two fields, exacerbated by the burden of past exploration costs, and have resulted in the delay of project for a few years, mostly due to finding potential gas buyer that can generate sufficient returns to the contractor. All of these factors define the marginality nature of the project. The main purpose of this study is to assess economic evaluation of North Kal gas development project in order to find the most suitable scenario under PSC scheme. The study was carried out with quantitative data analysis method with primary data obtained from internal source. Economic evaluation for all the scenarios proposed are calculated based on capital budgeting model with discounted cash flow, and referred to Production Sharing Contract (PSC) terms. Sensitivity analysis is also carried out to determine how different values of independent variables impacting the economic value of the project. The project investment decision comprises of strategic viewpoint were done based on technical approach and economic evaluation with capital budgeting model indicators, such as Net Present Value (NPV) and Internal Rate of Return (IRR). The finding shows that a flexibility in PSC terms are need to be made to improve the attractiveness of marginal project as well as to create an acceptable return for the contractor and fair revenue for Government of Indonesia (GoI). The study also shows that delay in project execution due to complex regulation could have significant impact to project’s revenue loss.